The rule of law in response to the COVID-19 emergency: a comparative analysis - Carlos Garrido López (Revista Catalana de Dret Públic, 2023)
This work presents an analysis of the measures adopted by leading democratic countries in response to the COVID-19 emergency, and the compatibility issues that arose between these measures and the guarantees of the rule of law. The global and simultaneous scope of this serious emergency facilitates comparative analysis and reveals their advantages and their shortcomings. The aim of the article is to evaluate the various extra-constitutional methods employed in response to the exception as well as the state of exception model, based on the regulation of extraordinary situations and the measures to be adopted. Lastly, the analysis focuses on the contradictions that have arisen as a consequence of the use and non-use of the state of exception model in the response to COVID-19 in Europe.